Characteristics of the gut microbiome profile in obese patients with colorectal cancer. Issue 4 (19th March 2021) - Shoji, Masakuni; Sasaki, Yu; Abe, Yasuhiko; Nishise, Shoichi; Yaoita, Takao; Yagi, Makoto; Mizumoto, Naoko; Kon, Takashi; Onozato, Yusuke; Sakai, Takayuki; Umehara, Matsuki; Ito, Minami; et al.
Abstract: Background and Aim: Obesity affects the gut microbiome, which in turn increases the risk for colorectal cancer. Several studies have shown the mechanisms by which some bacteria may influence the development of colorectal cancer; however, gut microbiome characteristics in obese patients with colorectal cancer remain unclear. Therefore, this study evaluated their gut microbiome profile and its relationship with metabolic markers. Methods: The study assessed fecal samples from 36 consecutive patients with colorectal cancer and 38 controls without colorectal cancer. To identify microbiotic variations between patients with colorectal cancer and controls, as well as between nonobese and obese individuals, 16S rRNA gene amplicon sequencing was performed. Results: Principal coordinate analysis showed significant differences in the overall structure of the microbiome among the study groups. The α‐diversity, assessed by the Chao1 index or Shannon index, was higher in patients with colorectal cancer versus controls. The relative abundance of the genera Enterococcus, Capnocytophaga, and Polaribacter was significantly altered in obese patients with colorectal cancer, whose serum low‐density lipoprotein concentrations were positively correlated with the abundance of the genus Enterococcus ; among the most abundant species was Enterococcus faecalis, observed at lower levels in obese versus nonobese patients. Conclusions: This study demonstrated several compositional alterations of the gut microbiome in patients with colorectal cancer and showed that a reduced presence of E. faecalis may be associated with obesity‐related colorectal cancer development. The gut microbiome may provide novel insights into the potential mechanisms in obesity‐related colorectal carcinogenesis. Abstract : This study demonstrated that a reduced presence of Enterococcus faecalis may be associated with the obesity‐related colorectal cancer development. The gut microbiome may provide novel insights for the potential mechanisms in obesity‐related colorectal carcinogenesis.